2007
DOI: 10.1021/jo070278a
|View full text |Cite
|
Sign up to set email alerts
|

1-Benzotriazol-1-yl-3,3,3-trifluoro-2-methoxy-2- phenylpropan-1-ones:  Mosher-Bt Reagents

Abstract: Benzotriazole derivatives of 3,3,3-trifluoro-2-methoxy-2-phenylpropionic acid react with water-soluble amino acids and peptides in an acetonitrile/water (2:1) mixture to give the corresponding amides in quantitative yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…An alternative approach to assign the absolute configuration of amino acids using the Mosher’s acid was developed by Katritzky et al [ 40 ]. N -acylbenzotriazoles are stable and crystalline derivatives of carboxylic acids and have advantages mainly when compared to acid chlorides that are unstable, moisture sensitive, difficult to prepare, and need to be stored in a deep freeze.…”
Section: 19 F-nmr Chiral Recognitionmentioning
confidence: 99%
“…An alternative approach to assign the absolute configuration of amino acids using the Mosher’s acid was developed by Katritzky et al [ 40 ]. N -acylbenzotriazoles are stable and crystalline derivatives of carboxylic acids and have advantages mainly when compared to acid chlorides that are unstable, moisture sensitive, difficult to prepare, and need to be stored in a deep freeze.…”
Section: 19 F-nmr Chiral Recognitionmentioning
confidence: 99%
“…Several benzotriazole sulfur reagents 130 have been prepared and used for thioacylations, thiocarbamoylations, alkyl/ alkoxythioacylations, and aryl/alkylthioacylations [186]. Benzotriazole of 3,3,3-trifluoro-2-methoxy-2-phenylpropionic acid (131) reacted with water-soluble amino acids and peptides in an acetonitrile/water (2 : 1) mixture to give the corresponding Mosher derivative in quantitative yield [187]. Anionic in situ generation of formaldehyde from benzotriazolylmethanol 132 has proved to be a very useful and versatile tool in synthesis [188].…”
Section: Benzotriazole-mediated Imidoylationmentioning
confidence: 99%
“…18 The Katritzky group also demonstrated that no racemization of the amino acid derivative occurred under the same conditions. 19 Bis-nucleophilic hydrazines were also reacted with carbamoyl benzotriazoles (Scheme 4 and Table IV). For methylhydrazine, the more electrophilic nitrogen atom (with methyl attached) was aminoacylated without any promoter and compounds 6a and 6b were obtained in excellent yields (Table IV, entries 1 and 2).…”
Section: Resultsmentioning
confidence: 99%